Not just sand: The folly of dismantling the environmental protection of dunes in Brazil. (January 2022) - Soares, Marcelo Oliveira; Barros, Eduardo Lacerda; Guerra, Renan Gonçalves Pinheiro
Abstract: The Brazilian federal government has followed an open agenda and land use policy against existing legislation in the past three years using the false argument that it hinders national development. A recent loss has been the repeal of national resolution CONAMA 303/2002. With the action of the Brazilian government to revoke this resolution, the mobile and eolian dunes are currently without legal national protection, and are available for real estate, industry (e.g., wind farms), and urban development, among other activities. In this context, the occupation of the mobile dunes promoted by the revocation of CONAMA 303 increases the risk of erosion of the beaches, damage to estuaries with mangroves, and destabilization of the coastline as a whole owing to the interruption of wind corridors of sand transport. The dunes are also one of the main freshwater reservoirs in Brazil. Therefore, the occupation of the dunes and encouragement of their impermeabilization by the attempted permanent repeal of CONAMA 303 resolution clearly puts the water security of Northeast Brazil (a semiarid region) at risk. This incentive to occupy mobile dunes by changing legislation will have a synergistic impact and amplify the predicted effects of climate change with negative repercussions on the sedimentary balance, tourist activities, and blue carbon sequestration. In addition, the vast quantity and value of goods and services provided to society and discussed in this article are sufficient to justify their conservation and a permanent decision from Supreme Court to keep the CONAMA 303 active. Graphical Abstract: ga1